2020
DOI: 10.1007/s00167-020-06244-6
|View full text |Cite
|
Sign up to set email alerts
|

A hinge position distal to the adductor tubercle minimizes the risk of hinge fractures in lateral open wedge distal femoral osteotomy

Abstract: Purpose To evaluate the incidence and morphology of medial cortical hinge fractures in lateral open wedge distal femoral osteotomy (LOW-DFO) and to determine a safe zone for the position of the osteotomy hinge to minimize the risk of hinge fractures. Methods Consecutive patients who underwent LOW-DFO for symptomatic valgus malalignment were screened for eligibility for this retrospective observational cohort study. Demographical and surgical data were collected. The incidence and morphology of medial cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 38 publications
2
35
2
Order By: Relevance
“…Measurements were performed as previously described [ 53 ] and modified for the CW-technique: on the preoperative hip–knee–ankle radiographs, the preoperative osteotomy planning conducted via mediCAD ® software (mediCAD Hectec GmbH, Altdorf, Germany) was identified and the wedge angle (angle α) and the height of the osteotomy wedge (interval “b”) were measured. In the postoperative standard AP radiographs, the length (interval “a”) and the inclination of the osteotomy (angle “ß”) were measured after identification of the osteotomy hinge and the anatomical axis of the femoral diaphysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements were performed as previously described [ 53 ] and modified for the CW-technique: on the preoperative hip–knee–ankle radiographs, the preoperative osteotomy planning conducted via mediCAD ® software (mediCAD Hectec GmbH, Altdorf, Germany) was identified and the wedge angle (angle α) and the height of the osteotomy wedge (interval “b”) were measured. In the postoperative standard AP radiographs, the length (interval “a”) and the inclination of the osteotomy (angle “ß”) were measured after identification of the osteotomy hinge and the anatomical axis of the femoral diaphysis.…”
Section: Methodsmentioning
confidence: 99%
“…For consecutive analysis, the two-dimensional position of the osteotomy hinge was assigned to a corresponding sector in a sector grid as previously described for LOW-DFO [ 53 ]. Bony landmarks (AT, medial femoral cortical bone, femoral condyles) were used to define two columns (M, L) and three rows (I, II, III) of the grid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biplanar technique facilitates the osteotomy to be more distal at the metadiaphyseal junction and reduces the risk of hinge fracture. 33 We find that using an external fixator to allow controlled correction reduces the risk of hinge fracture. If hinge fracture results in destabilization of osteotomy, contralateral screw or staple is an option.…”
Section: Complicationsmentioning
confidence: 89%
“…The incidence can be as high as 48% for medial closing wedge 31 and 39% 32 to 46% 33 in lateral opening wedge osteotomies. Although loss of correction and non-union of osteotomy have been attributed to it, Winkler et al 33 have also shown that in spite of high incidence of this complication in open wedge correction, there is no difference in the complication risk for patients with or without medial hinge failure. Common causes for medial cortex fracture are leaving a thicker medial bridge or too rapid opening of wedge.…”
Section: Complicationsmentioning
confidence: 99%